CULTURAL ECOLOGY AT YOUR FINGERTIPS: ANTHROPHOLOGY OF THE INDONESIAN ART SPECTRUM IN THE GRIP OF TECHNOLOGICAL EXTENSION AND ARTIFICIAL NARRATIVES - Elvis Elvis; Riswani Riswani (Journal of Social Science, 2026)
Objective: This study originates from a fundamental issue concerning the wave of technological extension infiltrating the core of traditional Nusantara arts, generating tension between preserving cultural authenticity and the inevitability of digital adaptation. Simultaneously, it introduces non-human actors such as algorithms and artificial narratives that actively reshape the cultural ecology. Method: Employing a literature review methodology, this research examines four interrelated problematic dimensions. Results: The findings reveal, firstly, that the transformation of traditional artistic practices occurs through a continuous negotiation between fluid authenticity and contextual digital adaptation, rather than a binary stance of rejecting or embracing technology. Secondly, digital platform algorithms function as gatekeepers of new cultural domains, altering the mechanisms of canonization and distribution of cultural artifacts, whereas artificial intelligence capable of instant meaning reproduction often lacks the emic dimension and cosmological depth that constitute the essence of traditional knowledge. Thirdly, the deconstruction of space and time due to digitalization detaches art from its sacred context, yet simultaneously creates liminal spaces where creative hybridity can flourish. Novelty: Fourthly, the crisis of knowledge authority triggered by artificial narratives is met by cultural practitioners through various strategies ranging from protective resistance to accommodative negotiation. This study concludes that the future of Nusantara arts in the digital era is not determined by technology itself but by the capacity of cultural agents to continuously and critically negotiate the balance between the sacred and the profane, the permanent and the mutable.